2004
DOI: 10.1620/tjem.202.93
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Mutagenic Effects of 2.45 GHz Radiofrequency Exposure in Spleen, Liver, Brain, and Testis of lacZ-Transgenic Mouse Exposed in Utero

Abstract: A possible mutagenic effect of 2.45 GHz radiofrequency exposure was examined using lacZ-transgenic Muta TM mice. Pregnant animals were exposed intermittently at a whole-body averaged specific absorption rate of 0.71 W/kg (10 seconds on, 50 seconds off which is 4.3 W/kg during the 10 seconds exposure). Offspring that were exposed in utero for 16 hours a day, from the embryonic age of 0 to 15 days, were examined at 10 weeks of age. To minimize thermal effects, the exposure was given in repeated bursts of 10 seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(9 citation statements)
references
References 24 publications
1
7
0
1
Order By: Relevance
“…12 In previous studies, it was reported that EMR produced from mobile phones may affect the immune, nervous, hematological and urinary systems as well as the cardiac functions, genetics and the normal growth and development of humans. [12][13][14] In their study, Ono et al 15 could not determine any significant difference in DNA mutation between the non-exposed group and the embryos exposed to EMR for 16 hours daily for 15 days. However, EMR produced from mobile phones appears to have harmful effects on the human body in two different ways.…”
Section: Discussionmentioning
confidence: 78%
“…12 In previous studies, it was reported that EMR produced from mobile phones may affect the immune, nervous, hematological and urinary systems as well as the cardiac functions, genetics and the normal growth and development of humans. [12][13][14] In their study, Ono et al 15 could not determine any significant difference in DNA mutation between the non-exposed group and the embryos exposed to EMR for 16 hours daily for 15 days. However, EMR produced from mobile phones appears to have harmful effects on the human body in two different ways.…”
Section: Discussionmentioning
confidence: 78%
“…However, we could not detect any changes in AO test outcome in the different animal groups. Ono et al (2004) used DNA sequence technique and indicated that RF of small bursts is not mutagenic in mouse when exposed in utero. Aitken et al (2005), using power electrophoresis, found a statistically significant genotoxic effect on epididymal sperm with damage to mitochondrial DNA and the nuclear ß‐globin locus.…”
Section: Discussionmentioning
confidence: 99%
“…2004). There is an absence of mutagenic effects of 2450‐MHz radio frequency exposure in various tissues of lacZ‐transgenic mice exposed in utero (Ono et al. 2004).…”
Section: Resultsmentioning
confidence: 99%